Keterkaitan Efisiensi Teknis dan Perilaku Risiko Petani Usahatani Bawang Merah Varietas Manjung - Rahmania Fajri, Siti; Fauziyah, Elys (Jurnal Hortikultura Indonesia, 2019)
Pojanan Village of Pamekasan District is wellknown as central producer for Manjung Variety of shallot. This variety has advantages such as high productivity, drought-resistant, pests and diseases resistant, fragrant aroma, and savory taste. However, there is low productivity problem that doesnot meet maximum potential expectation. Therefore, this study aimed to analyze the level of technical efficiency, farmers risk behavior, and interrelations between both issues. There were 42 respondents and the study involved analysis methods such us Cobb Douglass function by Stochastic Frontier approach, descriptive quantitative by Likert Scale, and Pearson Correlation. The result showed that average level of technical efficiency was about 77% with 40.5% neutral farmers risk behaviour and no significant relationship between technical efficiency and farmers risk behavior. Keywords: risk behavior, shallot production, technical efficiency